262. Pediatric Antibiotic Use in the Duke Antimicrobial Stewardship Outreach Network. (26th November 2018) - Smith, Michael; Ashley, Elizabeth Dodds; Anderson, Deverick J; Dyer, April; Jones, Travis; Johnson, Melissa; Davis, Angelina; Moehring, Rebekah W
Abstract: Background: The Duke Antimicrobial Stewardship Outreach Network (DASON) was established in 2013 to provide antimicrobial stewardship resources to community hospitals in the Southeast. Pediatric patients in community hospitals may benefit from antimicrobial stewardship program (ASP) activities. Methods: Antibacterial use (AU) was reviewed using the DASON Antimicrobial Stewardship Assessment Portal, which includes filters for National Healthcare Safety Network (NHSN) unit types. We performed a retrospective review of AU in pediatric units from January 1 to December 31, 2017. AU was summarized by days of therapy (DOT) and percent of total DOT for specific unit types and agents. AU rates were reported by DOT/1, 000 patient-days. Results: A total of 41 pediatric units were included from the 28 hospital DASON cohort: 11 Neonatal Critical Care or Step Down Nurseries, eight Pediatric Medical/Surgical Wards, and 22 Well Baby Units. There were no pediatric (non-neonatal) critical care or oncology units. A total of 21, 731 antibiotic DOT were attributable to pediatric units, accounting for 1.6% of all AU in the cohort. These include 5, 585 (26%) DOT in Neonatal Critical Care (level II/III) Units, 4, 898 (23%) in Pediatric Medical/Surgical Units, 3, 910 (18%) in Well Baby Units, 3, 307 (15%) in Neonatal Critical Care (level III) Units, 3, 217 (15%) in Step Down Neonatal Nurseries (level II), and 814 (4%) in Pediatric Medical Wards. Ampicillin (7, 229 DOT, 33%), gentamicin (6, 320 DOT, 29%), ceftriaxone (1, 750 DOT, 8%), and vancomycin (1, 462, 7%) were the most common antibiotics administered. AU rates were 219 DOT/1, 000 patient-days in children when compared with 979 in adults. Unit-specific rates ranged from 65 (Well Baby Units) to 1, 081 DOT/1, 000 patient-days (Pediatric Medical/Surgical Units). Rates in level II and III nurseries ranged from 302 to 697 DOT/1, 000 patient-days. Conclusion: Pediatric patients accounted for a small proportion of AU in community hospitals. AU rates on pediatric medical/surgical units were comparable with adult units. Although rates were lower in neonatal units, these units accounted for 75% of pediatric AU. Antibiotic exposure in the neonatal period has been associated with short- and long-term outcomes, including necrotizing enterocolitis, obesity, and atopy. This population would benefit from a dedicated focus from community hospital ASPs. Disclosures: All authors: No reported disclosures.